2022
DOI: 10.33706/jemcr.1107564
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of carbon monoxide intoxication and COVID-19

Abstract: Introduction This case report aimed to report two patients admitted to the emergency department with a preliminary diagnosis of carbon monoxide intoxication and was diagnosed with COVID-19 during their follow-up. Case 1 A 73-year-old female patient presented with weakness and shortness of breath complaints to the emergency department. Carboxyhemoglobin (COhgb) reached 36.2 %. Atypical pneumonic infiltration with peripheral and central patchy consolidations in the zones in hemothorax images fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…In a study, it was found that CoHb levels were higher in patients with bacterial sepsis than in patients hospitalized due to COVID-19. 53 - 56 In a study investigating the relationship between insulin-like growth factor-binding protein 5 (IGFBP5) expression and plasma osteopontin (OPN) levels and disease severity in COVID-19 patients, high OPN levels and low IGFBP5 levels were found to be associated with disease severity. 57 In a study examining the relationship between monocyte chemoattractant protein-1 and surfactant protein A levels and the clinical course and prognosis of COVID-19, both biomarkers showed a positive correlation with disease severity.…”
mentioning
confidence: 99%
“…In a study, it was found that CoHb levels were higher in patients with bacterial sepsis than in patients hospitalized due to COVID-19. 53 - 56 In a study investigating the relationship between insulin-like growth factor-binding protein 5 (IGFBP5) expression and plasma osteopontin (OPN) levels and disease severity in COVID-19 patients, high OPN levels and low IGFBP5 levels were found to be associated with disease severity. 57 In a study examining the relationship between monocyte chemoattractant protein-1 and surfactant protein A levels and the clinical course and prognosis of COVID-19, both biomarkers showed a positive correlation with disease severity.…”
mentioning
confidence: 99%